Effects of Blood Flow Restriction Training on Rehabilitaion of Patients Who Have Undergone Anterior Cruciate Ligament Reconstruction: A Narrative Review - Karami , Ali; Roostayi, Mohammad Mohsen; Hosseini , Seyed Majid (Journal of Clinical Physiotherapy Research, 2023)
The anterior cruciate ligament (ACL) tear and its subsequent reconstruction surgery can lead to many complications, such as strength deficit and muscle size reduction. Heavy load resistance training is an established method for improving muscle mass and strength but may be intolerable by patients recovering from ACL injuries due to its vigorous modality. Blood flow restriction (BFR) training is a novel technique which has been recognized as a promising alternative strategy, causing physiological adaptations with lower levels of resistance training and joint loading. Given the growing popularity of blood flow restriction, this narrative review seeks to explore the impact of BFR training on various facets of post-ACL reconstruction rehabilitation, comparing it to non-BFR training. A thorough literature search was conducted, and the effect of BFR training were examined on muscle strength, muscle size, pain, function, balance, comfort, willingness to use, bone mineral density, return to sport and ACL graft laxity. The results of this review suggests that BFR training post-ACL reconstruction may offer advantages in terms of muscle strength, muscle mass, bone mineral density, balance, knee joint pain, and function when compared to non-BFR training. However, there is a high variability in methodologies across existing studies, necessitating high-quality research with standardized methodologies and protocols to enable more effective application of BFR training in rehabilitation settings.